2017
DOI: 10.1038/nature23299
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring the taste system

Abstract: In mammals, taste buds typically contain 50-100 tightly packed taste receptor cells (TRCs) representing all five basic qualities: sweet, sour, bitter, salty and umami1,2. Notably, mature taste cells have life spans of only 5-20 days, and consequently, are constantly replenished by differentiation of taste stem cells3. Given the importance of establishing and maintaining appropriate connectivity between TRCs and their partner ganglion neurons (i.e. ensuring that a labeled line from sweet TRCs connects to sweet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 35 publications
(60 reference statements)
3
119
0
Order By: Relevance
“…How is information from this network of blood-sensitive neurons integrated to form the perception of blood? Experiments in Drosophila melanogaster and mice found that information from each taste quality remains segregated as each population projects to discrete regions in central taste-processing centers and activates different higher order neuronal populations (Chen et al, 2011;Harris et al, 2015;Lee et al, 2017;Marella et al, 2006). It will be interesting to see how signals from blood-sensitive subpopulations converge and if this processing stream is segregated from other subpopulations of stylet sensory neurons that do not respond to blood.…”
Section: Stylet Neurons Integrate Across Taste Qualities To Detect Bloodmentioning
confidence: 99%
“…How is information from this network of blood-sensitive neurons integrated to form the perception of blood? Experiments in Drosophila melanogaster and mice found that information from each taste quality remains segregated as each population projects to discrete regions in central taste-processing centers and activates different higher order neuronal populations (Chen et al, 2011;Harris et al, 2015;Lee et al, 2017;Marella et al, 2006). It will be interesting to see how signals from blood-sensitive subpopulations converge and if this processing stream is segregated from other subpopulations of stylet sensory neurons that do not respond to blood.…”
Section: Stylet Neurons Integrate Across Taste Qualities To Detect Bloodmentioning
confidence: 99%
“…How can ever‐changing bitter or sweet receptors find never‐changing neurons that must match the specificity of the signal? This article reviews a recent paper published in Nature (Lee, MacPherson, Parada, Zuker, & Ryba, , 548:330‐333) that identified two molecules belonging to the semaphorin axon guidance family of molecules ( SEMA 3A and SEMA 7A) that help maintain the “labeled line principle” between peripheral bitter or sweet receptors and their respective central projection area in the gustatory center.…”
mentioning
confidence: 94%
“…That question was answered in an elegant study from Charles Zuker and Nick Ryba's laboratories published in a recent paper in Nature (Lee et al., ). The authors have systematically looked for potential molecules among the gene expression profile of taste cells related to either adhesion molecules, growth factors, axon guidance molecules, or synaptic components.…”
mentioning
confidence: 99%
“…However, it also opens up a new avenue to tackle important problems to be solved in the future. Taste buds are densely packed with functionally distinct TBCs, each of which is innervated by secondary taste neurons in a quality-specific manner (Lee et al, 2017). How does a given nerve fiber selectively respond to ATP release from the target TBC, but not from adjacent cells?…”
mentioning
confidence: 99%